Intensification of a Lapita fishery at the Hopoate site on Tongatapu, Kingdom of Tonga - Wildenstein, Roxanne (My University, 2018)
Zooarchaeological analysis of fish bones is a valuable approach to understand prehistoric diet and resource exploitation in island and coastal settings. This thesis explores fish use at the Hopoate site on Tongatapu by identifying the various taxa which comprised the ichthyoarchaeological assemblage. The analysis focused on recovered materials which date to the earliest period of occupation in Tonga (2850 cal BP). This is the first detailed fishery study from Tongatapu; few have been conducted elsewhere in Tonga. The inhabitants at Hopoate focused fishing on inshore reef fish which is typical of Lapita fisheries. The first inhabitants, the Lapita peoples, benefited from a mixed subsistence economy of plant and marine foods. However, the relative contribution of fish to the Lapita diet was variable across the Pacific Islands. Eighteen fish taxa were identified from a total NISP of 5091. The analysis of fish bones from Hopoate indicated an intensification of the fishery during the mid-Lapita period (2690-2390 cal BP). Past archaeological studies on Tongatapu have recorded a severe decrease in the availability of shellfish from the Fanga ‘Uta Lagoon, following the initial settlement of the island. The increased fishing efforts are possibly related to the decreasing availability of shellfish from the lagoon.
Keywords: Tonga; Fishery; Lapita; Zooarchaeology